Designing Arabic Comic Based on Local Culture: تصميم القصة المصورة العربية (كوميك) المبنية على الثقافة المحلية - Munadia, Munadia (Al Mihwar: Jurnal Pendidikan Bahasa Arab dan Kebahasaan, 2024)
Instructional media is a fundamental component of educational activities, serving as teaching tools that assist educators in enhancing the teaching and learning process. It contributes in clarifying the information conveyed by teachers, thereby facilitating the achievement of educational objectives. This study aims to design an Arabic comic based on local wisdom as a medium for learning the Arabic language and to evaluate its feasibility. The research method used is research and development (R&D) with the ADDIE model, in which each development stage is systematically evaluated. The resulting product is a learning medium for the Al-Mihnah (professions) material. Validation results indicate that the comic received a score of 91.76% from material experts and 98.57% from media experts. A trial conducted on 12 fifth-grade students yielded a score of 89.5%, indicating that the Arabic comic based on local wisdom is highly suitable for use as a learning medium for the Arabic language. The findings imply that Arabic comics based on local wisdom can serve as effective and engaging instructional media, supporting language learning while promoting cultural values.